Corporate social responsibility, governance and corporate reputation - Gottschalk, Petter, 1950-; ProQuest (Firm) (Hackensack, N.J. : World Scientific, 2011)
"Expounds on the nature of white-collar crime and examines its relationship with corporate social responsibility, governance and corporate reputation. Presents different approaches for repairing damaged corporate reputations; explains how internal governance and investigations can be conducted. Discusses stages in corporate social responsibility and underscores knowledge management as an imperative tool to combat white-collar crime and build corporate reputation"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Corporations -- Corrupt practices; White collar crimes; Social responsibility of business; Corporate governance; Corporations -- Public relations; Electronic books